THE FACTORS WHICH INFLUENCE OF THE QUALITY OF REGIONAL GOVERNMENT FINANCIAL STATEMENT INFORMATION IN THE NORTH SUMATERA PROVINCIAL GOVERNMENT WITH GOVERNMENT INTERNAL CONTROL SYSTEM AS MODERATING VARIABLE - Nainggolan, Ronni (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was  to examine and analyze  the influence of the capacity of human resources, the use of information technology, the implementation of government accounting standard, and compliance with legal provisions with government  internal control system as moderating variable on the quality of financial statement information of the North Sumatra Provincial Government. The research used causality research method. The population was PPK-SKPD (Financial Administrative Personel-Regional Work Unit) personel Finance /Accounting Personel, and treasurers in 35 SKPDs in North Sumatra Provincial Government. The samples were 105 personel, taken by using total sampling technique. The data were gathered by using questionnaires. The hypothesis was tested by using multiple regression analysis and residual test with an SPSS software program. The result of the research showed that the capacity human resources, the use of information technology , the  implementation of government accounting standard, andcompliance with legal provisions had positive and significant influence on the quality of financial statement informationof the provincial government. Government  internal control system couldn’t moderate the correlation of the capacity of human resources, the use of information technology, the  implementation of government accounting standard, and compliance with legal provisions with the quality of financial statement information of the North Sumatra Provincial Government.